Academic Administration in Indian Universities: A Study of Occupational Efficacy, Managerial Aptitude and Organisational Commitment of Effective and Ineffective University Administrators - Sofal, Firdous Ahmad (INDIAN EDUCATIONAL REVIEW, 2016)
The present study was conducted to find out the occupational efficacy, managerial aptitude and organisational commitment of educational administrators working in Indian Universities. The descriptive method of research was adopted to carry out the study. A sample of 260 educational administrators was selected from the existing Universities of Jammu and Kashmir State. The Occupational Self Efficacy Scale (OSES) standardised by Pethe, Chowdari and Dhar (1999), Managerial Aptitude Scale (MAS) developed by Dhar, Dhar and Sharma (2011), and Organisational Commitment Scale (OCS) developed by Hyde and Roy (2011) were administered. The results revealed a significant positive correlation between occupational efficacy, managerial aptitude and organisational commitment of educational administrators in higher education. Besides, the results revealed a significant difference on all dimensions of managerial aptitude and organisational commitment of effective and ineffective educational administrators.